Reforming Budgetary Language - David Bradford (Center for Economic Studies and ifo Institute (CESifo), 2001)
In the context of several examples of problems associated with present budgetary conventions, I revisit Musgrave's conceptual division of the government's program into Allocation, Distribution and Stabilization Branch subbudgets. I suggest progress towards Musgrave's ideal of a more informative budgetary language, one less dependent on arbitrary institutional labeling, must be based on the nonarbitrary description of the individual's economic environment, as it is affected by government. As a first approximation, that environment can be summed up in terms of the individual's budget constraint and levels of public goods provided. Simple models suggest that an unambiguous budgetary language may be feasible but there remains much to clarify about both the objectives of the exercise and the specifics of methods to deal with particular problems.
Keywords: 330